Effect of endodontic irrigating solutions on the microhardness and roughness of root canal dentin: An in vitro study - Chetan R Patil; Veerendra Uppin (Wolters Kluwer Medknow Publications, 2011)
Context: To evaluate the effect of widely used endodontic irrigating solutions on root dentin microhardness and surface roughness. Materials and Methods: One hundred twenty, non-carious extracted human permanent incisor teeth were selected. The crowns of the teeth were sectioned and the roots were separated longitudinally to get 240 specimens. These specimens were then divided into six groups according to the irrigating solutions used. The solutions used were 5% and 2.5% NaOCl solutions, 3% H2 O2 , 17% EDTA solution, 0.2% chlorhexidine gluconate, and distilled water. Then, the specimens were subjected to microhardness and roughness testing. The data were analyzed using ANOVA and Tukey's multiple comparison tests. Results: The results of this study indicated that all irrigation solutions, except 0.2% chlorhexidine gluconate, decreased the microhardness of root dentin, and 3% H2 O2 and 0.2% chlorhexidine gluconate had no effect on surface roughness. Conclusions: Within the limitation of this study, it is concluded that 0.2% chlorhexidine gluconate seems to be an appropriate irrigation solution, because of its harmless effect on the microhardness and surface roughness of root canal dentin.